Regional earning disparities and the speed of transition: Evidence from Poland 1994-1997 - Fiona Burke; Patrick Paul Walsh (IZA Journal of Labor & Development, 2012)
In the early days of transition Poland hosted regional earning disparities. Low levels of worker and firm mobility allow us to threat regions as local labor markets. Wage behavior is modeled in regional labor markets as an outcome of the speed of transition examining employment restructuring in labor demand. The local shortterm unemployment (excessive layoffs) rate elasticity of pay is estimated as -0.29 and the local annual hiring rate elasticity of pay as + 0.75, controlling for individual characteristics and selection, amongst other factors. While individual characteristics determine participation rates and where one is on the wage distribution within regions, employment restructuring accounts for most of the mean earning disparities across regions.
Keywords: J6; L0; O5; 330; earnings; speed of transition and Polish regions; Regionale Lohnstruktur; Systemtransformation; Polen